Lipoprotein(a), family history of cardiovascular disease, and incidence of heart failure - Hai-Peng Wang; Na Zhang; Yu-Jie Liu; Tian-Long Xia; Guo-Chong Chen; Jing Yang; Fu-Rong Li (Journal of Lipid Research, 2023)
Lipoprotein(a) (Lp(a)) is a largely genetically determined biomarker for cardiovascular disease (CVD), while its potential interplay with family history (FHx) of CVD, a measure of both genetic and environmental exposures, remains unclear. We examined the associations of Lp(a) in terms of circulating concentration or polygenetic risk score (PRS), and FHx of CVD with risk of incident heart failure (HF). Included were 299,158 adults from the UK Biobank without known HF and CVD at baseline. Hazards ratios (HRs) and 95% Cls were estimated by Cox regression models adjusted for traditional risk factors defined by the Atherosclerosis Risk in Communities study HF risk score. During the 11.8-year follow-up, 5,502 incidents of HF occurred. Higher levels of circulating Lp(a), Lp(a) PRS, and positive FHx of CVD were associated with higher risks of HF. Compared with individuals who had lower circulating Lp(a) and no FHx, HRs (95% CIs) of HF were 1.36 (1.25, 1.49), 1.31 (1.19, 1.43), and 1.42 (1.22, 1.67) for those with higher Lp(a) and a positive history of CVD for all family members, parents, and siblings, respectively; similar results were observed by using Lp(a) PRS. The risk estimates for HF associated with elevated Lp(a) and positive FHx were attenuated after excluding those with incident myocardial infarction (MI) during follow-up. Lp(a) and FHx of CVD were independent risk factors for incident HF, and the highest risk of HF was observed among individuals with both risk factors. The association may be partly mediated by myocardial infarction.